Growth of the water fleas Daphnia magna (Straus, 1820) at different trophic levels of two small urban lakes in Indonesia - Livia Rossila Tanjung; Tjandra Chrismadha; Eva Nafisyah (LIMNOTEK Perairan Darat Tropis di Indonesia, 2023)
Nutrient enrichment in waters that has become a major environmental problem is related to excessive loading of nutrients into aquatic ecosystems. This nutrient enrichment, called eutrophication, favors phytoplankton growth, which can function as a natural daphnid feed. This study examined the growth performance of the water fleas Daphnia magna in water collected from small lakes (ponds) of different trophic levels. The water was taken from Situ Rawa Kalong, considered eutrophic from its dark green color, and the less eutrophic Situ Cibuntu with relatively clear water. Daphnids were grown in six aquaria filled with water from both ponds without artificial feeding with an initial density of five individuals/L. Samples of daphnids were taken every three to four days to observe their growth and reproduction, along with water samples to analyze the chlorophyll content and total suspended solids (TSS). The result showed that the eutrophic water of Situ Rawa Kalong favored phytoplankton growth, indicated by a consistently higher chlorophyll content in the water ranging from 35.3 to 140.7 μg/L compared to less eutrophic water of Situ Cibuntu with chlorophyll content ranging from 1.4 to 13.2 μg/L throughout the experiment. A much higher daphnid density of 151.7 individuals/L was achieved with more water chlorophyll content, meaning phytoplankton availability became a controlling factor for daphnid growth in the pond waters. This study reveals the functional relationships in the food chain between the water trophic level, the abundance of phytoplankton as the primary producer, and daphnids as the first-order predator. It also suggests that the open water trophic level can be managed to favor the daphnid growth, which can then be harvested for use as natural feed.